Helminth-derived stefin-1 selectively reduces leukemic cell viability and promotes apoptosis in U937 cells - Phornthip Ploensil; Yaneenart Suwanwong; Phatchariya Phannasil; Mayuri Tarasuk; Unchalee Thonsri; Pakkawan Prapasitsin; Pongsakorn Martviset; Pathanin Chantree (PLoS ONE, 2026)
Leukemia remains a challenging hematological malignancy, particularly due to treatment resistance and the limited availability of therapies that selectively target cancer cells. Helminth-derived cysteine protease inhibitors (stefins) are mainly known for their roles in host–parasite interactions, but their effects on cancer cells have not been well explored. In this study, we investigated the biological activity of recombinant Fasciola gigantica Stefin-1 (rFgStefin-1) in the human U937 leukemic cell line. Treatment with rFgStefin-1 reduced cell viability in a dose- and time-dependent manner, with an IC₅₀ of approximately 11 µM at 48 h. In contrast, normal peripheral blood mononuclear cells (PBMCs) showed minimal changes under the same conditions. Flow cytometry analysis demonstrated increased apoptotic cell populations together with mitochondrial membrane depolarization following rFgStefin-1 treatment. At the molecular level, rFgStefin-1 treatment was associated with an increased BAX/BCL-2 ratio, increased cleaved caspase-3 expression, reduced AKT-associated signaling, and enhanced PARP cleavage. These findings were supported by both qRT-PCR and Western blot analyses. Overall, these results suggest that rFgStefin-1 promotes apoptosis in leukemic cells while exerting limited effects on normal cells under the tested conditions. Further studies are required to clarify the underlying molecular mechanisms and to evaluate the effects of rFgStefin-1 in additional leukemia models and in vivo systems.